Automated Classification of Papillary Renal Cell Carcinoma and Chromophobe Renal Cell Carcinoma Based on a Small Computed Tomography Imaging Dataset Using Deep Learning - Zuo, Teng; Zheng, Yanhua; He, Lingfeng; Chen, Tao; Zheng, Bin; Zheng, Song; You, Jinghang; Li, Xiaoyan; Liu, Rong; Bai, Junjie; Si, Shuxin; Wang, Yingying; et al. (Frontiers in Oncology, 2021)
Objectives: To design and develop a framework utilizing deep learning (DL) to differentiate papillary renal cell carcinoma (PRCC) from chromophobe renal cell carcinoma (ChRCC) using convolutional neural networks (CNNs) on a small set of computed tomography (CT) images and provide a feasible method that can be applied to light devices. Methods: Training and validation datasets were established based on radiological, clinical and pathological data exported from the Radiology, Urology and Pathology Department. As the gold standard, reports were reviewed to determine the pathological subtype. Six CNN-based models were trained and validated to differentiate the two subtypes. A special test dataset generated with 6 new cases and 4 cases from The Cancer Imaging Archive (TCIA) was applied to validate the efficiency of the best model and manual processing by abdominal radiologists. Objective evaluation indexes (accuracy, sensitivity, specificity, receiver operating characteristic (ROC) curve and area under the curve (AUC)) were calculated to assess model performance. Results: The CT image sequences of 70 patients were segmented and validated by two experienced abdominal radiologists. The best model achieved 96.8640% accuracy (99.3794% sensitivity and 94.0271% specificity) in the validation set and 100% (case accuracy) and 93.3333% (image accuracy) in the test set. The manual classification achieved 85% accuracy (100% sensitivity and 70% specificity) in the test set. Conclusions: This framework demonstrates that DL models could help reliably predict the subtypes of PRCC and ChRCC.